Effect of Coronary Revascularization on the Prognostic Value of Stress Myocardial Contrast Wall Motion and Perfusion Imaging. Issue 6 (31st May 2017) - Gaibazzi, Nicola; Porter, Thomas; Lorenzoni, Valentina; Pontone, Gianluca; De Santis, Delia; De Rosa, Andrea; Guaricci, Andrea Igoren
Abstract : Background: The assessment of myocardial perfusion (MP) and wall motion (WM) using contrast dipyridamole echocardiography (cSE‐WMP) improves the sensitivity to detect coronary artery disease and the stratification of cardiac events, but its long‐term value for fatal and nonfatal ischemic cardiac events, also with respect to patients undergoing revascularization or not, remains to be determined. Methods and Results: One‐thousand three‐hundred and twenty‐nine patients with suspect or known CAD who underwent cSE‐WMP were followed for a median 5.5 years. The independent prognostic value of cSE‐WMP regarding cardiac death or nonfatal myocardial infarction was related to stress WM and MP, rest ejection fraction, clinical risk factors, and medications. Patients revascularized after cSE‐WMP were separately analyzed to determine whether the procedure influenced outcome and whether this depends on cSE‐WMP results. A total of 125 cardiac fatal and nonfatal ischemic events (9.4%) occurred during the follow‐up (61 deaths, 64 myocardial infarctions). The 5‐year event rate with normal MP and WM was 5.9%, 9.9% with isolated MP defects (normal WM), and 15.5% with both MP and WM abnormalities. In patients not undergoing revascularization (n=1111), reversible MP defects added discrimination value over WM response and clinical factors/medication data ( P =0.001), while in the cohort undergoing revascularization (n=218), cSE‐WMP results did not influence outcome. Conclusions: cSE‐WMP, with both contrast MP and WM assessments, provides independent, incremental prognostic information regarding ischemic cardiac events at 5 years in patients with known or suspected coronary artery disease. Revascularization reduces cardiac events after an abnormal cSE‐WMP, resulting in outcomes not different from those in patients with normal cSE‐WMP.